Perkembangan Penyakit Hawar Daun Bakteri pada Tiga Varietas Padi Sawah yang Diinokulasi pada Beberapa Fase Pertumbuhan - Andi Khaeruni; Muhammad Taufik; Teguh Wijayanto; Eko Aprianto Johan (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2014)
Bacterial leaf blight is an important disease of rice plant and could damage up to 50%. This study aimed to evaluate development of the bacterial leaf blight disease on three rice varieties which inoculated at various growth stage. The results of this study showed that IR64 variety which inoculated at seedling stage has shortest incubation period as well as disease severity i.e. 4.25 day after inoculation and 90%, respectively, while Cisantana variety which inoculated at generative stage showed the lowest of disease severity (< 40%). The highest number of panicles obtained on without inoculation treatment i.e an average of 10 panicles. Therefore growth stage and rice variety influenced to bacterial leaf blight disease development, the younger the plant infected, the faster the progression of the bacterial leaf disease. IR64 variety is highly susceptible to bacterial leaf blight disease.